In vivo study of the role of α6‐containing nicotinic acetylcholine receptor in retinal function using subtype‐specific RDP‐MII(E11R) toxin. Issue 1 (28th September 2016) - Barloscio, Davide; Cerri, Elisa; Domenici, Luciano; Longhi, Renato; Dallanoce, Clelia; Moretti, Milena; Vilella, Antonietta; Zoli, Michele; Gotti, Cecilia; Origlia, Nicola
Abstract : Although a6‐contaning (a6*) nicotinic acetylcholine receptors (nAChRs) are densely expressed in the visual system, their role is not well known. We have characterized a family of toxins that are antagonists for a6b2* receptors and used one of these [RDP‐MII(E11R)] to localize a6* nAChRs and investigate their impact on retinal function inadult Long‐Evans rats. Thea6*nAChRsinretinal tissuewere localized using either a fluorescently tagged [RDP‐MII(E11R)] or anti‐a6‐specific antibodies and found to be predominantly at the level of the ganglion cell layer. After intraocular injection of RDP‐MII(E11R) in one eye and vehicle or inactiveMII in contralateral eyes as controls, we recorded flash electroretinograms (F‐ERGs), pattern ERGs (P‐ERGs), and cortical visual‐evoked potential (VEPs). There was no significant difference in F‐ERG between the RDP‐MII(E11R)‐treated and control eyes. In contrast, P‐ERG response amplitude was significantly reduced in the RDP‐MII(E11R)‐injected eye. Blocking a6* nAChRs at retinal level also decreased the VEP amplitude recorded in the visual cortex contralateral to the injected eye. Because both the cortical and inner retina output were affected by RDP‐MII(E11R), whereas photoreceptor output was preserved, we conclude that the reduced visual response was due to an alteration in the function of a6* nAChRs present in the ganglion cell layer.—Barloscio, D., Cerri, E., Domenici, L., Longhi, R., Dallanoce, C., Moretti, M., Vilella, A., Zoli, M., Gotti, C., and Origlia, N. In vivo study of the role of α6‐containing nicotinic acetylcholine receptor in retinal function using subtype‐specific RDP‐MII(E11R) toxin. FASEB J. 31, 192–202 (2017) www.fasebj.org